Variation in seed traits among different eelgrass populations in China - Mingjie Liu; Xinhua Wang; Xiaochen Liu; Yu Zhang; Shidong Yue; Xiaomei Zhang; Shaochun Xu; Yi Zhou (Global Ecology and Conservation)
Sexual reproduction plays a crucial role in eelgrass population recruitment. Their seeds are important sexual reproduction organs and seed traits influence the maintenance and extension of eelgrass populations. In this study, the seed morphology, germination, and biochemical composition of different eelgrass populations in China were investigated. The findings showed that (1) the volume and weight of eelgrass seeds varied by four to five times among different individuals, and this variation among populations was a result of their adaptation to specific local environmental conditions; (2) the differences in seed germination time were determined by intrinsic factors rather than by environmental conditions during the germination period; (3) sugars were the most important energy supply substance for eelgrass seeds and the arginine, glutamic acid, aspartate, linoleic acid, palmitic acid, and oleic acid contents were relatively high in eelgrass seeds. These intraspecific variations among different eelgrass populations reflect environmental adaptations and the results provide essential information and foundational data that can be used to improve large-scale seed-based eelgrass restoration projects.